Microalbuminuria as an indicator of sepsis and to predict mortality in patients admitted in intensive care unit - Shamsudeen, Faris K.; Legha, R.; Shaji Kumar, K.; Chandran, Jinu (International Journal of Research in Medical Sciences, 2025)
Background: Sepsis remains a major cause of morbidity and mortality worldwide. Early recognition is critical, but conventional diagnostic methods such as culture require more than 24 hours, delaying targeted therapy. Microalbuminuria, a marker of systemic endothelial dysfunction and capillary leak, may provide a rapid and non-invasive predictor of outcome. Objective of this study was to assess the role of microalbuminuria in predicting mortality among patients with sepsis admitted to the intensive care unit (ICU). Methods: This prospective observational study was conducted in the ICU of Travancore Medical College, Kollam, from August 2022 to January 2024. A total of 122 adult patients with sepsis were enrolled after applying inclusion and exclusion criteria. Spot urine samples were collected within 6 hours of admission (ACR1) and at 24 hours (ACR2) to measure the albumin–creatinine ratio (ACR). The change in ACR (ΔACR = ACR1-ACR2) was calculated. Associations of ACR values with mortality and ICU stay were analysed using non-parametric tests, correlation studies, and ROC curve analysis. Results: ACR2 was significantly higher among non-survivors than survivors (mean 284.3 vs. 77.0, p<0.001). Survivors showed a significant decline in ACR between 6 and 24 hours, while non-survivors had a significant increase. ΔACR correlated negatively with ICU stay duration (ρ = -0.303, p<0.001). ROC analysis identified ΔACR ≤21.5 as the optimal cutoff for predicting mortality, with sensitivity 83.9%, specificity 86.9%, and accuracy 86.2%. Conclusions: Serial measurement of urine ACR, particularly ΔACR, within the first 24 hours is a simple, rapid, and cost-effective predictor of mortality in sepsis and can be especially valuable in resource-limited settings.